Nonelite exercise‐related injuries: Participant reported frequency, management and perceptions of their consequences. Issue 2 (27th August 2013) - Grice, A.; Kingsbury, S. R.; Conaghan, P. G.
<x xml:space="preserve">Abstract</x> This mixed methods study explored the frequency of sport/exercise‐related injuries in nonelite sport, participant‐reported management and perceptions of potential injury consequences. Focus group participants, who trained two to four times a week and had previously sustained musculoskeletal sports‐related injuries, reported seeking medical advice secondary to advice from teammates or online research. General practitioners were viewed as gatekeepers to specialist secondary care and less able to effectively treat sport‐related injuries. Participants displayed limited awareness of potential future implications of injury, and considered physical and psychological benefits of exercise more valuable than potential injury‐associated risks. In the survey of physically active people, over half reported sustaining an exercise‐related injury (562/1002, 56%). Previously injured respondents were less likely to consider consulting a health professional for injury‐related advice than those with no injury history (45% vs 64%; P < 0.001) and more likely to continue exercising despite injury (51% vs 37%; P < 0.001). Concerns about injuries largely related to short‐term issues; only 32% were concerned about possible long‐term joint problems including osteoarthritis. Exercise‐related injury was common in nonelite exercise participants. There was some dissatisfaction with care pathways for sports‐related injuries and a lack of awareness about appropriate injury management and potential consequences of injury, particularly in the long‐term.